The effectiveness of implementing the HACCP system to ensure the quality of food products in regions with ecological problems - Baikadamova, Assemgul; Yevlampiyeva, Yelena; Orynbekov, Duman; Idyryshev, Berik; Igenbayev, Aidyn; Amirkhanov, Shyngys; Shayakhmetova, Madina (Frontiers in Sustainable Food Systems, 2024)
This study developed and implemented a specific HACCP plan for the meat pate “Phirmennyi” at the small meat processing enterprise “Alteev” in Semey, Kazakhstan. The research, conducted in collaboration with the Department of Food Production Technology and Biotechnology at Shakarim University, was carried out in an area affected by the ecological consequences of the former Semipalatinsk Nuclear Test Site. The study aimed to identify critical control points (CCPs) and assess potential risks following the Technical Regulations of the Customs Union. Additionally, it evaluated the effectiveness of the HACCP plan in reducing contaminants, such as heavy metals, radionuclides, and pesticides, while considering the region’s environmental impact on food safety and quality. Standard procedures were followed for hazard analysis, CCP identification, setting critical limits, monitoring, corrective actions, verification, and record-keeping. Heavy metals were measured using inductively coupled plasma mass spectrometry, while Cs-137 radionuclides were analyzed with scintillation and semiconductor gamma spectrometers. Statistical analysis was conducted in Microsoft Excel to compute mean values, standard deviations, and correlations, with significance defined at p ≤ 0.05. Five CCPs were identified during the production of an experimental batch of meat pâté, including raw material acceptance, blanching, cooking, cooling, and packaging/storage. Implementing this plan resulted in a reduction in contaminants, including a decrease in lead from 0.55 to 0.51 mg/kg, arsenic from 0.12 to 0.07 mg/kg, and Cs-137 from 7.2 to 6.8 Bq/kg. By addressing both the contaminants and the specific environmental context of the region, this research demonstrates the critical role of a well-structured food safety plan. The HACCP system not only improved food quality but also ensured compliance with safety standards, providing reassurance to consumers. This case study advocates for broader adoption of food safety management in regions with similar ecological challenges, promoting a more sustainable and secure food supply chain.